Incidência de restrição de crescimento extrauterino e fatores de risco e proteção associados em recém-nascidos de muito baixo peso - Kerolaynne Fonseca de Lima; Suianny Karla de Oliveira Macedo; Arthur Pedro Marinho; Camila Dayze Pereira Santos; Lorena de Carvalho Monte de Prada; Ana Cláudia Moraes Medeiros de Lima; Ana Verônica Dantas de Carvalho; Anna Christina do Nascimento Granjeiro Barreto (Residência Pediátrica, 2022)
OBJECTIVE: To determine the incidence of extrauterine growth restriction (RCEU) in very low birth weight (VLBW) newborn and associated factors. METHODS: Longitudinal, prospective study with very low birth weight premature newborns in a maternity school, carried out between October/2017 to September/2018. Demographic, clinical and nutritional variables were evaluated. The curves used at birth and to monitor growth were those of the INTERGROWTH Project. RCEU was defined as a Z score of birth weight < -2. In inferential statistical analysis, chi-square, Students t, Mann-Whitney and logistic regression tests were used. RESULTS: 97 children were analyzed, of which 41.2% developed RCEU. Weight, Z score at birth and caloric intake in the first week of life were higher in children without growth restriction. The use of mechanical ventilation, length of stay in intensive care unit, bronchopulmonary dysplasia and late sepsis were associated with RCEU in the bivariate analysis. In multivariate logistic regression, only the Z score of birth weight (p<0.001) and the use of mechanical ventilation (p=0.006) remained associated with the outcome. Regarding the nutritional status at birth, the higher the Z score of weight, the lower the incidence of RCEU. CONCLUSION: The incidence of RCEU found was high, with the nutritional status at birth and the use of mechanical ventilation as the main associated factors.